Awareness and Perception of Breast Cancer among the Future Healthcare Providers of Ras Al Khaimah, United Arab Emirates - Syed Arman Rabbani, Hala Mutasem, Ranin Abdul Naser, Yousra Hussein (Journal of Applied Pharmaceutical Science, 2017)
Breast cancer is the most common type of cancer and the most common cause of cancer-related mortality among women worldwide. Breast cancer represents the second leading cause of deaths among women in United Arab Emirates (UAE) and is a growing public health issue in the country. The present study was aimed at assessing the level of awareness and perception regarding breast cancer among the students of RAK Medical and Health Sciences University, Ras Al Khaimah, UAE. It was a cross sectional study in which a pre-tested and validated questionnaire regarding breast cancer was distributed to the students and their responses were recorded. Out of the total 200 students, majority (75.5%) were female. The mean knowledge score of medical students was highest 9.17 ± 1.54 out of a maximum of 10, as compared to 8.28 ± 2.39 of nursing students, 8.04 ± 1.68 of dental students and 7.68 ± 2.01 of pharmacy students. However, the mean perception score of pharmacy students was the highest 3.43 ± 1.29 out of a maximum of 5 when compared to 3.28 ± 1.30 of dental students and 3.07 ± 1..50 of medical students. Female students had higher level of knowledge regarding breast cancer as compared to male students. However, in case of perception both the female as well male students possessed similar level of perception. The level of knowledge and perception improved as the year of study advanced. The study also showed that as the level of knowledge regarding breast cancer increased the perception of the students towards breast cancer improved fortifying the importance of knowledge in changing perception of people towards diseases like breast cancer.
Keywords: Breast cancer, Awareness, Healthcare Providers, United Arab Emirates.